4P Marketing Mix Communication Strategy Through Instagram @mierah_purwantoro - Syahputri, Nabilla Sukma Ayudhia; Santoso, Budi (Institut Agama Islam Negeri (IAIN) Curup, 2025)
In today's culinary business, there are more and more competitors, therefore a marketing strategy is needed that can attract the attention of consumers so that the business can continue to grow. The purpose of this research is to describe the 4p marketing mix communication strategy used to expand the marketing of @mierah_purwantoro. This research uses descriptive qualitative method with data collection using interviews with the owner, admin, employees, and consumers, observation, and documentation. The results of this study indicate that: 1) SWOT analysis in the @mierah_purwantoro culinary business, namely: Strengths, strategic location, prioritizing service quality, pure raw materials, affordable prices, and accepting online purchases or delivery. Weaknesses, namely large business capital and a less broad target market. Opportunities, using various social media for promotion and creating new menus. Threats, namely the number of new competitors and similar marketing strategies with other similar businesses. 2) The 4p marketing mix communication strategy applied in marketing the @mierah_purwantoro culinary business, namely: Product (product), has a variety of quality product variants. Price (price), has an affordable price that matches the quality of the products offered. Place (place) is strategic. Promotion, through Instagram by uploading photos and videos on snapgrams or instastory, creating content with celebrities, including the place and WhatsApp number of the owner and admin, and creating independence competitions or other days.